A STUDY OF EXCHANGE STRUCTURES IN METRO TV’S "AFTER HOURS" PROGRAM - Susie Chrismalia Garnida, Riskha Fidhiya Aulia (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This study reports an analysis on the exchange structure in conversation between the hosts and the callers in Metro TVâ€™s â€œAfter Hoursâ€ Â English program. The purpose of this study is to find out the types of initiating â€“ responding acts produced by the hosts and the callers. Adopting Strenstromâ€™s theory (1994) as the theoretical framework, this study uses the qualitative approach Â to examine ten (10) conversations in the â€œAfter Hoursâ€ program. The analysis shows that there are certain exchanges of initiating â€“ responding acts which match Strenstromâ€™s theory. However there are also exchanges that do not match the theory. The study found that 18 points in the ten conversations do not match Strenstromâ€™s theory. The possible reasons for this mismatch include the fact that the host and the callers share a common knowledge, and the addressee wants to give information to the speaker to correct the speakerâ€™s assumption. Despite the occasional unmatched responses, the conversation goes well and the speakers can understand each other well. Â